Quality analysis of quality control system in work units based on the Routine Data Quality Assessment of X Hospital in Semarang District - Endang Fatmawati; Farid Agushybana; Septo Pawelas Arso (Public Health and Preventive Medicine Archive, 2020)
Background and purpose: An excellent process of hospital quality management system produces useful data for the management in the future decision-making. The problem obtained from the quality management system of X hospital was that the data collectors do not understand the procedure of data collection, thus the data became less complete and less accurate. Routine Data Quality Assessment (RDQA) instrument is recommended to measure the data quality. This study aims to analyze the data quality in the quality management system of X Hospital work unit in Semarang. Methods: Quantitative method was applied in this study using cross-sectional approach. RDQA instrument was used as a model of quality assessment of routine data that can be implemented to evaluate the quality of the collected data. Purposive sampling was used in the selection of informants. This study involved 22 quality managers at level I (the wards) as the informants who conducted the data selection, three quality managers at level II as data collectors, and one quality manager at level III as a data center. The data were analyzed both quantitatively and qualitatively. The work units assessed in this study include the outpatient, inpatient and critical units. Result: RDQA instrument was adapted by adjusting the substanceof RDQA with the standards of hospital accreditation in Indonesia. The development of indicator 2 focused on the understanding of data collection, while indicator 3 focused on the supervision of data collection, and indicator 5 focused on the staff understanding on the recommendation of quality achievement results. The application of RDQA articulated that the quality control systems did not optimally run, including the lack of understanding of the data collection procedure, non optimal supervision of quality management, not all quality manager conduct data verification properly, not all staff understand the recommendations of the quality achievement results. The highest percentage of the data quality was 93% and the lowest was 72%. In general, the system assessment was 1.5-2.5 which indicated that the data were partially complete/available/ operated. Conclusion: RDQA resulted that the data quality control on the hospital quality management system has not yet to be conducted optimally.